Knowledge, attitudes and acceptance of voluntary medical male circumcision among males attending high school in Shiselweni region, Eswatini: a cross sectional study - Mirriam Hlelisani Shezi; Boikhutso Tlou; Saloshni Naidoo (BMC, 2023)
Abstract Background In countries such as Eswatini, where there is a high HIV prevalence and low male circumcision the World Health Organization and the Joint United Nations Programme for HIV/AIDS recommend infant and adult circumcision be implemented. The aim of this study was to assess the knowledge, attitudes and acceptability of voluntary medical male circumcision amongst males attending high school in Eswatini. Methods An observational cross-sectional study was conducted during February and March of 2018 amongst 407 young males (15-21 years) attending Form 4, in nine high schools in the Shiselweni region of Eswatini using a self-administered questionnaire of 42 close ended questions. Sociodemographic details, circumcision status, acceptance of voluntary medical male circumcision, knowledge and attitude scores analysed in Stata® 14 statistical software were described using frequencies, medians and ranges respectively. Bivariate and multivariate linear regression was used to assess the impact of independent variables on circumcision status and acceptance of voluntary medical male circumcision. The level of statistical significance was p < 0.05. Results Amongst the 407 high school-going males, 48.98% (n = 201) reported being circumcised. The majority of the adolescents (75.74%; n = 306) were knowledgeable about voluntary medical male circumcision. However, an even larger majority (84.90% (n = 343) had a negative attitude towards it. In the multivariate logistic regression analysis, having parented their own children (aOR: 3.55; 95%CI: 1.2-10.48), and having circumcised friends (aOR: 3.99; 95%CI: 1.81-8.84) were significantly associated with being circumcised. Neither knowledge nor attitude were associated with the acceptability of voluntary medical male circumcision. Conclusion In Eswatini male high school students are knowledgeable about voluntary medical male circumcision but have a negative attitude towards it. Having parented their own children, and having circumcised friends influenced being circumcised.